THE MAIN ASPECTS OF TEACHING FOREIGN LANGUAGES ON THE BASIS OF MODERN EDUCATIONAL METHODS (Conferencea, 2023)
Language learning is one of the important areas of attachment in the personality society. The medium of communication the language in the natural environment in the family, among the public or it is possible to master practical in an organized way. While knowledge of linguistic phenomena theoretically taught.